ANALISIS PERAN MATA KULIAH PKN DALAM MENINGKATKAN RASA BELA NEGARA MAHASISWA DI PRODI PPKN FKIP UNIVERSITAS RIAU - Saputra, Muhamad Untung; Eddison, Ahmad; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by a sense of defending the State which is very much needed by students, especially the PPKn FKIP study program, Riau University because the sense of defending the State is an obligation for all Indonesian people, defending the State is the attitude and behavior of citizens who are inspired by their love for the Republic of Indonesia based on Pancasila and the Constitution. 1945 in establishing the survival of the nation and state. State defense carried out by students can be in the form of non-physical state defense, namely all actions that can show love for the homeland in the sustainability of the Republic of Indonesia. Attitudes and behaviors that are imbued with a sense of love for the Republic of Indonesia are obtained through the subject of Citizenship Education, the formulation of the problem in the research, namely how is the role of PKN courses in increasing the sense of state defense of students in the PPKn FKIP Study Program, Riau University?. The purpose of this study is to find out how the role of PKN courses in increasing the sense of state defense of students in the PPKn FKIP Study Program, Riau University. The benefits of the results of this study are a source of learning for all parties, especially students of the Civics Study Program in order to maintain a sense of defending the country and increasing the sense of defending the country. This research method is descriptive quantitative, the data collection instruments used in this study are observation, questionnaires ), and interviews consisting of 25 questions and supported by data obtained through documentation. The population in this study were students of the Riau University Civics Study Program. Sampling from the entire population was taken using Slovin's opinion and to determine the respondents consisting of 68 people from the 2017-2019 class the researchers used a purposive sampling technique and the data were analyzed using the formula P = f/n x100%. Based on the results of the research conducted, it can be concluded that the overall data regarding the Analysis of the Role of PKN Courses in Improving Students' Sense of State Defense at the PPKn FKIP Study Program, Riau University, amounted to (92.04%) which was in the range of 75.01%-100%. Thus, it can be concluded that the Analysis of the Role of PKN Courses in Improving Students' Sense of State Defense at the PPKn FKIP Study Program, Riau University is